2023
DOI: 10.1021/acsenergylett.3c00622
|View full text |Cite
|
Sign up to set email alerts
|

Reviving Inactive Lithium and Stabilizing Lithium Deposition for Improving the Performance of Anode-Free Lithium–Sulfur Batteries

Abstract: Anode-free lithium–sulfur batteries (AFLSBs) show a surprisingly prolonged cycle life 2-fold higher than anode-free lithium metal batteries. The principal difference is the presence of an intrinsic polysulfide (PS) shuttle between electrodes in AFLSBs. However, the underlying mechanism for the impact of PS redox species on the electrochemical performance of AFLSBs is not clearly understood. Herein, we investigate the role of PS redox species in retrieving inactive lithium for compensating lithium inventory los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The first is that the LiPSs of the cathode electrode diffuse to the anode electrode side and deposit on the lithium surface; the second is the participation of lithium salt in the formation of solid electrolyte interlayer (SEI). Recent studies have shown that a small amount of LiPSs and LiNO 3 as electrolyte additives can effectively suppress the dendrite problem of lithium metal anodes . After using the CoP@NPC-S electrode, the metal lithium anode remains flat and smooth after 100 cycles, indicating that a small amount of LiPSs shuttle to the anode side does have a positive effect on stabilizing the lithium anode.…”
Section: Resultsmentioning
confidence: 99%
“…The first is that the LiPSs of the cathode electrode diffuse to the anode electrode side and deposit on the lithium surface; the second is the participation of lithium salt in the formation of solid electrolyte interlayer (SEI). Recent studies have shown that a small amount of LiPSs and LiNO 3 as electrolyte additives can effectively suppress the dendrite problem of lithium metal anodes . After using the CoP@NPC-S electrode, the metal lithium anode remains flat and smooth after 100 cycles, indicating that a small amount of LiPSs shuttle to the anode side does have a positive effect on stabilizing the lithium anode.…”
Section: Resultsmentioning
confidence: 99%